An evaluation of near patient tests for detecting herpes simplex virus type-2 antibody. Issue 5 (1st October 2000) - Saville, Melanie; Brown, David; Burgess, Christine; Perry, Keith; Barton, Simon; Cowan, Frances; Palu, Giorgio; Mengoli, Carlo
Abstract : Objectives: To examine the "in use" test characteristics of the POCkit "near patient" HSV-2 rapid test for the detection of HSV-2 IgG antibodies for use in the clinic. This test relies on a visual interpretation of the result. Methods: 2093 serum samples, 229 from UK and 919 from Italian genitourinary medicine clinic patients and 945 from obstetric and gynaecology clinic patients in Italy were tested. Tests were carried out according to manufacturers' protocol in the United Kingdom and Italy. Three readers independently recorded a score for each test carried out and the results were compared. Results: In the UK study, the three readers disagreed on the result on 5.2% of tests. In the Italian study, there was disagreement in 10.2% of tests. Conclusions: This study has demonstrated a problem in the subjective nature of the interpretation of the POCkit HSV-2 test. It highlights the need for adequate training of clinic staff and the need for clinics to adopt policies of quality assurance and ongoing monitoring which will ensure the validity and accuracy of this clinic based test.